(3MGTjI Ydi TQM OjHGLI GdeUHGMs - (3jYbhH Hf Ydj (B((3SjO Ydj(B) (3GdHQhShjs
(3ChdgG (B:s
(3hHYO, ajbhd jYbhH Hf SjO Ydj gPg ahGFO bO bjOJgG Ydi TQM OjHGLI GdeUHGM s
(3BNQgG (B:s
(3EPG de jcf GdHMK ef LgI GdYGedjI jdRe KHhJ GdNGeS HGdGSJbQGA aj CLRGA GddHGH hCHhGHg Je s
(3GdeUHGM dCHj GdaJM GdeWQRjs
(3HgG CKQ WeSs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs